C-reactive protein-albumin-lymphocyte index predicts biochemical recurrence in prostate cancer - Özdeş, Ahmet Alper; Sesli, Mustafa; Başaranoğlu, Mert; Karakeçi, Ahmet; Orhan, İrfan; Akbay, Erdem (Canadian Urological Association, 2026)
Systemic inflammation and nutritional status influence prostate cancer outcomes. The C-reactive protein-albumin-lymphocyte (CALLY) index integrates these parameters, but its ability to predict biochemical recurrence (BCR) is not well-established. In a single-center, retrospective cohort of 600 patients (2018–2022), the pre-treatment CALLY index was calculated as [albumin (g/dL) × lymphocytes (cells/µL)]/[CRP (mg/dL) × 10?]. Patients were stratified by D'Amico risk. BCR was defined as prostate-specific antigen (PSA) ?0.2 ng/mL after radical prostatectomy (confirmed) or ?2.0 ng/mL above nadir after radiotherapy. Kaplan-Meier and Cox models evaluated associations; model performance was assessed using receiver operating curve (ROC), C-index, net reclassification improvement (NRI), and decision-curve analysis (DCA). Over a median followup of 28.4 months, 26.8% developed BCR. The optimal CALLY threshold was 1524.2, demonstrating modest discriminative ability (area under the curve [AUC] 0.684, 95% confidence interval [CI] 0.624–0.744; sensitivity 72.4%, specificity 64.8%). Low CALLY was associated with higher 36-month BCR rates (31.4% vs. 21.6%; log-rank p=0.042). In multivariable analysis, CALLY independently predicted BCR both as a continuous measure (per 100-unit increase: HR 0.882, 95% CI 0.778–0.998, p=0.048) and dichotomized at the median (HR 0.798, 95% CI 0.642–0.992, p=0.042), alongside baseline PSA and Gleason ?4+4. Adding CALLY modestly improved discrimination of CAPRA (C-index 0.71?0.74) and Memorial Sloan Kettering Cancer Center (MSKCC) (0.73?0.76) models, with NRI 0.246 (p=0.006) and net clinical benefit on DCA across 10–40% thresholds. Effects were most pronounced in high-risk and surgically treated patients. The pre-treatment CALLY index represents a readily available biomarker that independently predicts BCR and may complement established risk stratification tools in prostate cancer, although model performance was modest. External validation in prospective cohorts with longer followup is necessary before clinical implementation. © 2026 Canadian Urological Association
Keywords: albumin; C reactive protein; prostate specific antigen; adult; aged; androgen deprivation therapy; Article; biochemical recurrence; cancer patient; cancer radiotherapy; cohort analysis; controlled study; diagnostic test accuracy study; follow up; human; lymphocyte; lymphocyte count; major clinical study; male; prostate cancer; radical prostatectomy; receiver operating characteristic; retrospective study; sensitivity and specificity